2011
DOI: 10.1007/s10773-011-0905-9
|View full text |Cite
|
Sign up to set email alerts
|

Factorization of Integrals Defining the β-Function into Integrals of Total Derivatives in N=1 SQED, Regularized by Higher Derivatives

Abstract: Some calculations in supersymmetric theories, made with the higher derivative regularization, show that the β-function is given by integrals of total derivatives. This is qualitatively explained for the N = 1 supersymmetric electrodynamics in all orders.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…(1.3) is equal to the number of loops L in the original supergraph, while the number of momentum integrations in the right hand side is equal to L − 1. Some explicit calculations made with the higher derivative regularization have demonstrated that the integrals in the left hand side are integrals of total derivatives [39,51] and even of double total derivatives [40,43,53,54,56]. Due to this feature it is possible to calculate one of the momentum integrals and obtain the same number of momentum integrations in both sides of eq.…”
Section: Jhep04(2018)130mentioning
confidence: 99%
“…(1.3) is equal to the number of loops L in the original supergraph, while the number of momentum integrations in the right hand side is equal to L − 1. Some explicit calculations made with the higher derivative regularization have demonstrated that the integrals in the left hand side are integrals of total derivatives [39,51] and even of double total derivatives [40,43,53,54,56]. Due to this feature it is possible to calculate one of the momentum integrals and obtain the same number of momentum integrations in both sides of eq.…”
Section: Jhep04(2018)130mentioning
confidence: 99%
“…Subsequently, the results of the papers [44,45] were written in the form of integrals of double total derivatives [46][47][48]. However, the versions of the higher covariant derivative regularization which were used for making explicit calculations for the non-Abelian N = 1 supersymmetric theories break the BRST invariance [49,50] (while the background gauge invariance is not broken).…”
Section: Jhep05(2016)014mentioning
confidence: 99%
“…We choose masses of the Pauli-Villars fields so that they will be proportional to the parameter Λ in the higher derivative term [50,55]:…”
Section: Introductionmentioning
confidence: 99%